Chemical Properties and Proximate Composition of Pellonula leonensis Fish from the Congo River and Nanga Lake - Mambou, Léa Béatrice; Loumouamou, Bob Wilfrid; Dzondo, Gadet Michel (European Journal of Applied Sciences, 2024)
Pellonula leonensis is a small fish, with a maximum size of around 102,8 mm, consumed in Congo Brazzaville, most of which comes from the Congo River and Nanga Lake. For the nutritional importance of Pellonula leonensis fish in the diet of Congolese populations, this study aims to determine the proximate composition of this fish. The moisture content was obtained after drying the samples in an oven at 70°C for 24 hours. The total lipid content was determined after Soxhlet extraction. The Kjeldahl method was used to determine total protein content. Total soluble sugars were determined using the phenol and sulphuric acid method of Dubois et al. The total ash content was measured after incineration in a muffle furnace at 550°C. Magnesium, phosphorus and calcium contents were measured by atomic absorption spectrometry. Regarding the Pellonula leonensis fish studied, the protein content varies from 38.71 to 39.93%, from 40.27 to 41.12% and from 39.75 to 39.96% respectively for the dried fish of Brazzaville, Boko and Pointenoire. Lipid levels vary from one source to another, with levels of around 20% and 30% respectively in samples from Nanga Lake and the Congo River. The carbohydrate content ranged from 2.01 (± 0.09) to 4.88 (± 0.07)% for samples from the Congo River and from 8.14 (± 1.22) to 9.26 (± 0.95)% for samples from Nanga Lake. The samples studied gave ash contents ranging from 13.95 ± 1.01 to 15.81 ± 0.79 % for both origins. The crude fibre content varied from 0.26 to 0.29%, from 0.30 to 0.33% and from 0.37 to 0.39% respectively for samples from Brazzaville, Boko and Pointe-Noire.